Islamic Religious Rituals in the Era of Society 5.0: Implications for Religious Identity in Pluralistic Society - Wahyu Hidayat; Muhammad Faza Ikhram Hidayat; Wahyu Hidayat (Universitas Halu Oleo (UHO), 2025)
Religion, which was originally eternal and timeless in human life, sometimes has to deal with the passage of time from time to time. Technology and religion sometimes merge as a result of how human life evolves over time. One of the results of life events is technology, which sometimes develops and brings the latest advances to mankind. This research uses a literature study conducted through research from books, journals, or other written documents of a scientific nature which are then constructed and analyzed to draw conclusions. The results of this study show that there are some differences in Islamic religious rituals performed in the era of society 5.0, and then there is a shift in the meaning of religious rituals in the era of society 5.0, and a correlation between the influence of the era of society 5.0 in shaping Islamic religious identity in a pluralistic society.